2000
DOI: 10.1007/s002280000157
|View full text |Cite
|
Sign up to set email alerts
|

The consumption of drugs by 75-year-old individuals living in their own homes

Abstract: Almost all 75-year-old persons receive drugs. The observed polypharmacy may increase drug-related risks. The discrepancies between the GPs' knowledge of their patients' medication and the actual intake may involve a potential risk. A better registration of the patients' total medication and the implementation of a common medication database for the use of all involved physicians may improve medication and reduce risks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
120
1
8

Year Published

2001
2001
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 166 publications
(143 citation statements)
references
References 0 publications
14
120
1
8
Order By: Relevance
“…It is also possible that a medication review enhances adherence, by improving the patientdoctor relationship, or by emphasising the relevance of medications. Polypharmacy is common in older people 27 , and it has been suggested that reviewing and possibly reducing the number of medications might help adherence 28 . Number of medications was not a significant predictor of non-adherence in our study.…”
Section: Possible Interventionsmentioning
confidence: 99%
“…It is also possible that a medication review enhances adherence, by improving the patientdoctor relationship, or by emphasising the relevance of medications. Polypharmacy is common in older people 27 , and it has been suggested that reviewing and possibly reducing the number of medications might help adherence 28 . Number of medications was not a significant predictor of non-adherence in our study.…”
Section: Possible Interventionsmentioning
confidence: 99%
“…Appropriate medication use -a key factor to maximize therapeutic benefits and to minimize the risk of ADRs -is known to be a major concern in this patient group. For example, Barat et al performed interviews with 75-year-old home-dwelling persons in Denmark and found that more than 80% of them used three or more drugs, and that non-adherence was prevalent (20 to 70% depending on the measuring method) (4,5). Tordoff et al interviewed communitydwelling people aged ≥75 years in New Zealand and observed problems with reading and understanding drug labels (9 and 4%, respectively) and leaflets (12 and 6%), and difficulty with swallowing solid dosage forms (14%) (6).…”
Section: Introductionmentioning
confidence: 99%
“…Already in 1987 Gilchrist et al showed up to two thirds of patient's drug history obtained from the general practitioner to be inaccurate (9). It has since then repeatedly been proven that GP records (5; 6; 8; 2; 4) as well as hospital records (3; 4) and even patient reporting (5; 7; 3; 4) shows major discrepancies when compared to more thorough medication reviews, with up to 25 % of prescribed drugs being used without the general practitioners knowledge (2). A Danish study suggests that the use of a nationwide database may prove to be the most accurate measure of actual drug use (3).…”
Section: Introductionmentioning
confidence: 99%